Motivasi Dan Disiplin Kerja Terhadap Kinerja Pekerja PT Sri Indah Mandiri Di Kota Batam - Indra, Giska; Suhardi, Suhardi (LPPM Universitas Putera Batam, 2021)
Competitive advantage will be achieved if company management can manage company activities by promoting human resources or better known as effective and efficient employees. One of the factors that determine good employee performance is Work Motivation and Discipline because Human Resources are an important element in determining good or bad for the company.PT Sri Indah Mandiri Focuses on providing hardware for architectural and building needs. The purpose of this study is to determine and analyze the effect of work motivation and discipline on the performance of PT Sri Indah Mandiri employees either partially or simultaneously. In this study the population used 120 samples with variables are motivation (X1) and work discipline (X2) and employee performance (Y). In this study, the analytical method used is linear regression analysis, to test the truth of the final hypothesis that has been done by the researcher. Hypothesis testing is done by using the F andT test. The results of the study show that partial motivation has a significant effect on employee performance and work discipline has a significant effect on employee performance. Motivation and Work Discipline simultaneously have a positive and significant impact on the performance of employees of PT Sri Indah Mandiri.